1996
DOI: 10.1287/opre.44.1.50
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Method for Performance Evaluation of Kanban Controlled Production Systems

Abstract: The aim of this paper is to develop a general purpose analytical method for performance evaluation of multistage kanban controlled production systems. We consider a single-part type production system decomposed into stages in series. Each stage consists of a manufacturing cell and an output buffer. With each stage is associated a given number of kanbans. The kanban controlled production system is modeled as a queueing network with synchronization mechanisms. The basic principle of the proposed approximation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 26 publications
2
67
0
1
Order By: Relevance
“…The extension of the EKCS to assembly systems leads to two kanban release mechanisms as was the case in the extension of the KCS to assembly systems (Di Mascolo and Dallery, 1996). These mechanisms are the Simultaneous EKCS (SEKCS) and the Independent EKCS (IEKCS) and are described in detail next.…”
Section: Extended Kanban Control Systems For Assembly Systemsmentioning
confidence: 95%
See 1 more Smart Citation
“…The extension of the EKCS to assembly systems leads to two kanban release mechanisms as was the case in the extension of the KCS to assembly systems (Di Mascolo and Dallery, 1996). These mechanisms are the Simultaneous EKCS (SEKCS) and the Independent EKCS (IEKCS) and are described in detail next.…”
Section: Extended Kanban Control Systems For Assembly Systemsmentioning
confidence: 95%
“…Although this situation is highly prevalent in the industry, not much work has been done in analyzing it. In Sbiti et al (1999) the BSCS is extended to assembly systems, and in Di Mascolo and Dallery (1996) the KCS is extended to assembly systems. In the latter case, an important additional (with respect to the serial system case) control element arises having to do with the way in which component parts and kanbans are released prior to assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, their kanban system is equivalent to a system of buffers in tandem working under the minimal blocking policy (Bonvik et al, 1997). In another approach, Di Mascolo et al (1996) applied product-form approximations with load-dependent service times to solve the subsystems. Baynat et al (2001) showed how to extend the earlier productform approximation methods to more general kanban systems such as assembly and disassembly systems, but still with only one type of product.…”
Section: Introductionmentioning
confidence: 99%
“…We assume general service-time distributions at the server nodes and both saturated input supply and output demand. The saturation assumption is intended to simplify our development, and the proposed framework can easily be modified to handle unsaturated supply and demand (Di Mascolo et al 1996). The framework is unified for a general class of blocking protocols for the following reasons: (i) a common set of modeling tools such as the kanban characterization of queueing systems, synchronization stations that link the flows from a production cell to the next, closed queueing analysis of circulating kanbans within a cell, and open system analysis of the production stage queues in the cells are used in each blocking protocol; (ii) a common strategy for cell-level analysis and a common iterative algorithm for approximating over the cells in a serial line are used; and (iii) the same approach is used for approximating both open and closed queueing systems.…”
mentioning
confidence: 99%
“…Studies on BCQN systems are much fewer in number because of the additional complexity arising out of a fixed number of pallets circulating in such systems (Onvural 1990). The work of Di Mascolo et al (1996) is perhaps a first approximation scheme for BOQN systems under minimal blocking. General blocking, which encompasses all types of blocking was introduced by Cheng and Yao (1994).…”
mentioning
confidence: 99%